"Perpustakaan Manusia" as a Knowledge-Sharing Medium to Enhance Interaction Between Social Groups - Auliya Noviyani Sardi; Agus Rusmana; Ute Lies Khadijah (Indonesian Journal of Librarianship, 2025)
Abstract  Background/Problem Statement: "Perpustakaan Manusia" is a knowledge-sharing program in the field of mental health, initiated by "Menjadi Manusia" in January 2023. In the phydigital era, this program offered direct contact with social groups that faced public prejudice or remained unfamiliar to Library Users. Purpose: This study aimed to explore the implementation of the "Perpustakaan Manusia" program as a knowledge-sharing medium to enhance interaction between social groups. Method: A qualitative study was conducted with a descriptive method, and data were collected using observation, literature study, and social media. Analysis comprised data reduction, display, and verification stages. Result: The primary information sources in the implementation of the "Perpustakaan Manusia" were humans from various social groups who often experienced prejudice and were called "Pustaka". In this study, the information recipients were referred to as "Pemustaka". Each "Pustaka" had a title derived from background experiences or knowledge. The "Perpustakaan Manusia" had Golden Rules that must be followed throughout the event. Knowledge sharing related to the title attached to the "Pustaka" lasted approximately ±15 minutes. Meanwhile, Pemustaka were allowed to ask questions, discuss, and share stories. On October 3, 2025, the "Perpustakaan Manusia" had been held 13 times and included 69 individuals. Conclusion: : The implementation of the "Perpustakaan Manusia" can serve as a knowledge-sharing medium that enhances interaction between social groups.